Performance and ergonomic evaluation of direct paddy seeder and mechanical rice transplanter in wet lands - RATHOD SACHIN RAVSU; Dr. P.K Suresh Kumar (Guide) (Tavanur 2013 Department of Farm Power, Machinery and Energy)
Performance and ergonomic evaluation of direct paddy seeder and mechanical rice transplanter in wet lands
Performance and ergonomic evaluation of direct paddy seeder and mechanical rice transplanter in wet lands